Improving Performance of SMK 75 Dua Purwokerto Business Center Through Entrepreneurial Orientation - SARAH DIEN HAWA; Achmad Syauqi; Angga Ari Prasetya; Mia Anjani (Journal of Society, Community and Business Development, 2024)
The decline in the number of SMK graduates who are absorbed in the world of work is a major problem in all SMKs. One of strategy to prepare graduates capability of entrepreneurship so that students and teachers are able to develop entrepreneurial interests as a place to practice business. The school business center is the main activity in the field of entrepreneurship as well as a place to develop competencies according to student majors. Some of the problems that occur are (1) Lack of interest in managing the business center causes business performance to be not optimal. (2) Sales are still very lacking. (3) Business profits and profits are not as expected. (4) Business center managers consisting of students and teachers have not been maximized in conducting business promotions. (5) Has not made the right marketing strategy to develop its business center. Keywords: Bussiness Center, Enterpreneurial orientation, Performance